Konflik Sosial Dalam Sengketa Tanah Di Sukahaji Kota Bandung Dalam Persepektif Sosiologi Hukum - Muhammad Rafli Permanayudha; Chisa Belinda Harahap (Jurnal Hukum Jurisdictie, 2026)
This study examines the social conflict arising from land disputes in Sukahaji, Bandung City, from the perspective of legal sociology. Employing a qualitative approach with descriptive methods, the research aims to identify the triggering factors of the conflict, analyze its impacts on local community life, and understand the interaction patterns among parties (community, government, and developers). The findings reveal that the conflict is triggered by clashes between the historical-social claims of the community and formal state law, exacerbated by urbanization, power imbalances, and limited community participation. Its impacts include social tensions, economic vulnerabilities, and psychological pressures, while interaction patterns reflect the dominance of government and developers over local communities, prompting resistance through social solidarity. This study underscores the importance of participatory and equitable conflict resolution approaches to strengthen inclusive social order.